Altered Patterns of the Fractional Amplitude of Low-Frequency Fluctuation and Functional Connectivity Between Deficit and Non-Deficit Schizophrenia - Zhou, Chao; Tang, Xiaowei; You, Wei; Wang, Xiang; Zhang, Xiaobin; Zhang, Xiangrong; Yu, Miao (Frontiers in Psychiatry, 2019)
Objective: A limited number of studies have previously reported on the regional activity (amplitude of low-frequency fluctuation, ALFF) and functional integration (functional connectivity, FC) of whole brain in deficit schizophrenia (DS). The present study investigates the resting-state characteristics of the fractional ALFF (fALFF) and the FC in both DS and non-deficit schizophrenia (NDS) patients, and further explores their correlations with neurocognitive features. Methods: Demographic, resting-state functional MRI, and neurocognitive data were collected from 33 DS and 41 NDS male patients, as well as in 40 male healthy controls (HCs). The voxel-wise fALFF was measured to evaluate regional cerebral function. Regions with differences in fALFF between DS and NDS patients were used as seed points in whole-brain FC analysis. Partial correlation analysis was conducted to examine associations between the fALFF or the FC of altered regions and neurocognitive assessments. Results: Both patient groups showed decreased fALFF in the sensorimotor area, visual cortex, and frontoparietal pathway, but increased fALFF in the precuneus and middle cingulate gyrus when compared with the HCs. Moreover, the NDS group demonstrated higher fALFF than HCs in the left thalamus, caudate, and hippocampus. Compared with the NDS group, the fALFF of the visual cortex was specifically increased, but that of the bilateral insula, the anterior cingulate gyrus, and the regions extended to the frontotemporal cortex was decreased in DS group. Numerous abnormal FCs of nerve pathways were found between two patient groups, mainly concentrated in the frontooccipital, frontotemporal, insula-visual cortex, as well as the temporooccipital pathway. Correlation analysis indicated that, in the DS group, the FC value between the left insula and the visual cortex was positively correlated with cognitive flexibility. In the NDS group, the fALFF of the right insula was negatively correlated with speech fluency and the FC value between the ACG and the visual cortex was positively correlated with visual spatial memory. Conclusion: The present study demonstrates different altered patterns of fALFF and FC between male DS and NDS. The specific altered regions of the SN associated with impaired neurocognition in male DS patients suggest novel insights into the pathogenesis of cognitive impairment in schizophrenia.